ANALISIS KINERJA PENGELOLAAN KEUANGAN DAERAH DI KOTA BAUBAU TAHUN 2001-2016 - Syamsir Nur (JEP (Jurnal Ekonomi Pembangunan), 2020)
This research was conducted on the government of the City of Bau-Bau with the aim to determine the performance of regional financial management in the City of Bau-Bau 2001-2016. The data used is secondary data sourced from the BPS office of Bau-Bau City and analyzed using financial ratio analysis consisting of decentralization ratios, dependency ratios, independence ratios, effectiveness ratios and efficiency ratios.Has research concluded that the city of Bau-Bau has a decentralization ratio, regional financial dependency ratio and a low independence ratio and is on a scale of 10 percent, however the effective ratio shows the city of Bau-Bau is effective in the use of financial funds with the above percentage 90 percent that is more than 100 percent so it is not efficient. The performance of this financial management also shows that the city of Bau-Bau has a relatively high regional expenditure, which can be seen from regional spending with greater realization.